Effect of Native Grass Substitution with Jengkol (Archidendron jiringa) Peel on Sheep Performance. Issue 1 (March 2020) - Hidayah, N; Lubis, R; Wiryawan, K G; Suharti, S; Rita, W; Nurhaita,
Abstract: The effect of substitution native grass with jengkol ( A. jiringa ) peel on sheep performance was investigated. Three treatments substitution of jengkol peel (0, 15, 22.5%) were five replications in a randomized block design. This research used 15 sheep with body weight around 15-27 kg. The jengkol peel and concentrate were given in pellet form to reducing the strong odor from jengkol peel. Substitution of jengkol peel at 22.5% increased feed intake (746, 74 g/h/d) but did not affect on every daily gain and feed efficiency. The more substitution of jengkol peel change the texture of pellets become more compact and solid so increased the palatability and lead to the feed intake increased. It is concluded that native grass can be substituted with jengkol peel until 22.5% to increase feed consumption of sheep